Student Participation in Campus Public Administration Processes: Opportunities and Challenges at the Lombok Business Academy - Juliyati, Neneng (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to analyze the forms, driving factors, and obstacles to student participation in the public administration process at the Lombok Business Academy (AKBIL) as an effort to realize transparent and participatory campus governance. In the context of vocational higher education, students have a strategic role as recipients and supervisors of internal public services. However, their involvement is often still administrative in nature and does not touch on the decision-making aspect. This study uses a qualitative approach with a case study method that focuses on the phenomenon of student participation in the campus public administration system. Data were obtained through in-depth interviews, observations, and documentation studies of students, administrative staff, and campus leaders. The results show that student participation in AKBIL has developed through various activities such as completing service evaluation questionnaires, using the Academic Information System (SIKAD), and involvement in student organizations and communication forums with the administration. This study concludes that student participation is an important component in the implementation of good governance principles in the university environment. To strengthen this role, AKBIL needs to develop participatory policies that ensure the sustainability of student-administration forums, improve digital literacy among the academic community, and